(untitled) (مجلة أبحاث قانونية, 2023)
This study addresses the seizure of crime-recovered objects in the Libyan criminal legislation. A comparative study of Egyptian legislation according to two directions; the first is a description of the objects that the competent authority may seize with an indication of the procedures that the Libyan legislator requires to be followed for the legality of the seizure; secondly: to clarify the scope of disposing of the seized objects by discussing the provisions of returning the seized objects first, which advances a legislative rule according to which every person who claims a right in the seized objects may ask the investigator to hand the same over to him, and in case of refusal he may complain before the Court of First Instance to request that his statements be heard before the court; as for the second, it is concerned with the extent of the legality of confiscating seized objects, a procedure which purpose is for the state to forcibly acquire seized objects related to the crime on behalf of their owner without compensation. It is an optional, complementary penalty for felonies and misdemeanors, unless the law stipulates otherwise. On the other hand, confiscation may be obligatory, as required by public order, as it relates to something inherently outside the scope of dealin. Thus, confiscation in this regard is a preventive measure that must be taken against everyone